1997
DOI: 10.1093/ndt/12.8.1608
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis: evaluation with colour duplex ultrasonography

Abstract: Colour duplex US with calculation of the RI and delta RI of intrarenal arteries is a valuable non-invasive test assessing the haemodynamic effects of a RAS. Low costs and safety support the use of the Doppler technique in screening for renovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
7

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 4 publications
2
38
0
7
Order By: Relevance
“…Intrarenal Doppler parameters such as decreased flow velocity, low RI (<0.50) and PI values, decreased acceleration (<3 m/s 2 ) and increased acceleration time (>70 m/s) are also considered in renal artery stenosis (Bude and Rubin 1995). Comparison of intrarenal RI and PI values on the side with pathology with the contralateral kidney also improves diagnostic success in unilateral renal artery stenosis (Krumme et al, 1996;Riehl et al, 1997). Another study suggested that the normal early systolic peak that should normally be observed disappears (Stavros et al, 1992).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Intrarenal Doppler parameters such as decreased flow velocity, low RI (<0.50) and PI values, decreased acceleration (<3 m/s 2 ) and increased acceleration time (>70 m/s) are also considered in renal artery stenosis (Bude and Rubin 1995). Comparison of intrarenal RI and PI values on the side with pathology with the contralateral kidney also improves diagnostic success in unilateral renal artery stenosis (Krumme et al, 1996;Riehl et al, 1997). Another study suggested that the normal early systolic peak that should normally be observed disappears (Stavros et al, 1992).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…None of the 325 patients that were included in this study had an hilar acceleration time Ͼ100 mm/s or had evidence of kidney atrophy (Ͻ9 cm in length), parameters that are suggestive of renal artery stenosis Ͻ60% (10,11). Furthermore, no patients with renal insufficiency were included in this study if they had a mean resistance index value Ͻ0.45, a value associated with bilateral renal artery stenosis, or a difference in resistance index values Ͼ8% between the two different kidneys, a value associated with the presence of unilateral renal artery stenosis (12). We also assessed the effects on resistance index values of a Ͼ25% difference in kidney size (estimated by length ϫ width ϫ 0.5).…”
Section: Measurement Of Intrarenal Arterial Resistance Indexmentioning
confidence: 99%
“…However, patients with known renal artery stenosis were excluded, and we accounted for Doppler intrarenal indexes that have been previously reported to be associated with the presence of hemodynamically significant renal artery stenosis (12). Also, eliminating patients with asymmetrical kidney size (Ͼ25%) did not alter the finding that resistance index values were elevated to a similar extent in subjects with renal insufficiency regardless of albuminuric status.…”
Section: The Effect Of Ras Inhibition On Intrarenal Resistance Indexmentioning
confidence: 99%
“…Sensitivity of up to 92% and specificity of up to 95% for detection of severe RAS (greater than 70%) have been reported. [29][30][31] Generally, it was found that moderate renal artery narrowing (50-70%), did not produce convincing Doppler waveform changes in the intra-renal vessels. These studies also found that peripheral renal Doppler studies could not always reliably distinguish severe stenosis from complete occlusion.…”
Section: Ultrasoundmentioning
confidence: 96%